A Mechanism of Virus-Induced Demyelination. (16th May 2010) - Das Sarma, Jayasri
Abstract : Myelin forms an insulating sheath surrounding axons in the central and peripheral nervous systems and is essential for rapid propagation of neuronal action potentials. Demyelination is an acquired disorder in which normally formed myelin degenerates, exposing axons to the extracellular environment. The result is dysfunction of normal neuron-to-neuron communication and in many cases, varying degrees of axonal degeneration. Numerous central nervous system demyelinating disorders exist, including multiple sclerosis. Although demyelination is the major manifestation of most of the demyelinating diseases, recent studies have clearly documented concomitant axonal loss to varying degrees resulting in long-term disability. Axonal injury may occur secondary to myelin damage (outside-in model) or myelin damage may occur secondary to axonal injury (inside-out model). Viral induced demyelination models, has provided unique imminent into the cellular mechanisms of myelin destruction. They illustrate mechanisms of viral persistence, including latent infections, virus reactivation and viral-induced tissue damage. These studies have also provided excellent paradigms to study the interactions between the immune system and the central nervous system (CNS). In this review we will discuss potential cellular and molecular mechanism of central nervous system axonal loss and demyelination in a viral induced mouse model of multiple sclerosis.